On the order of relative approximation of classes of differentiable periodic functions by splines - Babenko, V. F.; Parfinovych, N. V. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
In the case where n → ∞, we obtain order equalities for the best L_q -approximations of the classes W_p^r , 1 ≤ q ≤ p ≤ 2, of differentiable periodical functions by splines from these classes.